2018
DOI: 10.1021/acs.orglett.8b00493
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetric Construction of Remote Vicinal Quaternary and Tertiary Stereocenters via Direct Doubly Vinylogous Michael Addition

Abstract: An asymmetric direct doubly vinylogous Michael addition has been developed for the generation of sterically congested vicinal quaternary and tertiary stereocenters. This doubly vinylogous Michael addition of β,γ-unsaturated butenolides to 3-methyl-4-nitro-5-alkenyl isoxazoles, powered by a bifunctional squaramide, affords a broad range of densely functionalized enantioenriched γ,γ-disubstituted butenolides in high yields with excellent diastereo- and enantioselectivities in most cases. Moreover, the strategy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…Our research group reported the first use of vinylogous deconjugated butenolides 8 in a 1,6‐conjugate addition reaction in 2018 [44a] . Cinchonidine‐derived catalyst C18 was employed to carry out this highly selective reaction between butenolides 8 and 3‐methyl‐4‐nitro‐5‐alkenylisoxazoles 52 (Scheme 30).…”
Section: Vinylogous Conjugate Addition (Vca) Reactionsmentioning
confidence: 99%
“…Our research group reported the first use of vinylogous deconjugated butenolides 8 in a 1,6‐conjugate addition reaction in 2018 [44a] . Cinchonidine‐derived catalyst C18 was employed to carry out this highly selective reaction between butenolides 8 and 3‐methyl‐4‐nitro‐5‐alkenylisoxazoles 52 (Scheme 30).…”
Section: Vinylogous Conjugate Addition (Vca) Reactionsmentioning
confidence: 99%
“…Previously, the group of Jørgensen, has described the organocatalytic doubly vinylogous 1,6‐Michael addition of alkylidene lactones to 2,4‐dienals and later Dixon has explored the addition of γ ‐butyrolactam to cyclic dienones (Scheme ). The organocatalytic direct doubly vinylogous addition of γ ‐substituted butenolides to 1,6‐Michael acceptor such as 3‐methyl‐4‐nitro‐5‐alkenyl‐isoxazoles is rarely reported . The γ ‐substituted butenolides and 3‐methyl‐4‐nitro‐5‐alkenyl‐isoxazoles are attractive vinylogous partner as their heterocyclic cores are found in large number of bioactive natural products and pharmaceuticals ,,.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Therefore, much attentionh as been given to the development of synthetic methods allowing for their preparation, in particulari nas tereocontrolled manner. [3][4][5][6] The most commona pproachr elies on the application of dienolates A for their preparation.I th as been demonstrated that silyloxy furans serve as their synthetic equivalents readily participating in the vinylogous Mukayama-aldol or Mukayama-Michael and related reactions proceeding in ar egioselective fashion in the 5-position of the furan ring. [4,5] It is also possible to generated ienolates A from 5-substituted-3H-furan-2-ones (a-Angelica Lactone and relateds ystems) or 5-substituted-5H-furan-2-ones under Brønstedb ase catalysis conditions.…”
mentioning
confidence: 99%
“…[4,5] It is also possible to generated ienolates A from 5-substituted-3H-furan-2-ones (a-Angelica Lactone and relateds ystems) or 5-substituted-5H-furan-2-ones under Brønstedb ase catalysis conditions. [6,7] Within this research area, the asymmetrico rganocatalysis [8] has provenh ighly useful, providing valuable solutions leading to enantiomerically enriched g,g-disubstituted butenolides. [5,6] Given the importance of g,g-disubstitutedb utenolides, we becamei nterested in the development of an alternative synthetic strategy for their preparation.…”
mentioning
confidence: 99%
See 1 more Smart Citation